Substantial Reduction of High Level Radioactive Waste by Effective Transmutation of Minor Actinides in Fast Reactors Using Innovative Targets - Yamawaki, Michio; Konashi, Kenji; Fujimura, Koji; Takeda, Toshikazu (IntechOpen, 2012)
None